Method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seed crystal method

Through the clear liquid alkali mineralization route and heterophase seed crystal method, the environmental friendliness and repeatability challenges of all-silicon CHA molecular sieve membranes are solved, and efficient CO2/CH4 separation performance and high-quality film preparation are achieved. Carbon capture applications.

CN119113820APending Publication Date: 2024-12-13NANJING TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411319208.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-21
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art has problems such as environmentally unfriendly fluoride use, difficulty in ensuring repeatability, long synthesis time and difficult to control film thickness when preparing all-silicon CHA molecular sieve membranes, especially in high humidity flue gas carbon capture applications. , there are limitations in traditional fluorine mineralization routes and secondary hydrothermal methods.

Method used

The clean liquid alkali mineralization route and heterophase seed crystal method are used instead of the traditional fluorine mineralization route and secondary hydrothermal method. The preparation and carrier pretreatment of MFI molecular sieve seed crystals are constructed with hydrothermal synthesis technology to build high-quality Si- CHA molecular sieve membrane reduces the probability of intergranular pore formation and improves the density and repeatability of the membrane.

Benefits of technology

It significantly improves the repeatability and performance of Si-CHA molecular sieve membrane, shortens the synthesis time, achieves efficient CO2/CH4 separation performance, and reduces environmental impact. It is suitable for carbon capture applications such as natural gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113820A_ABST
    Figure CN119113820A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing a Si-CHA molecular sieve membrane by a heterogeneous seed crystal method, which adopts clear liquid alkali to mineralize fluorine-free sol, and prepares a high-performance Si-CHA molecular sieve membrane on a porous carrier by the heterogeneous seed crystal method, and comprises the following steps: (1) preparing an MFI molecular sieve seed crystal; (2) pretreating a porous carrier; and (3) preparing the Si-CHA molecular sieve membrane by a heterogeneous seed crystal method. According to the method, semi-solid gel is replaced by clear liquid with good fluidity, a porous carrier or crystal layer can be uniformly infiltrated, air on the surface and pore channels of the carrier or crystal can be removed, and meanwhile, the mass transfer rate in a liquid state is obviously higher than that in a semi-solid state, so that the intergranular pore formation probability is greatly reduced. The Si-CHA molecular sieve membrane prepared by the invention has high chemical stability and hydrothermal stability, and is suitable for capturing carbon dioxide from natural gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve membrane materials and relates to a method for preparing a Si-CHA molecular sieve membrane, in particular to a method for synthesizing a Si-CHA molecular sieve membrane by a heterogeneous seeding method. Background Art

[0002] Climate change caused by greenhouse gas emissions has become a major ecological and environmental problem facing the world. The power industry is an important source of carbon emissions in my country, accounting for about 36% of total carbon emissions (Carbon Energy, 2023, e362). The development of low-energy and high-efficiency carbon capture technology has become a hot topic in current research.

[0003] Membrane separation has the remarkable characteristics of high efficiency and energy saving. The precise construction of membrane materials with high stability and high CO2 separation performance is the research focus of membrane-based efficient carbon capture. Polymer membranes have successfully achieved industrial application of CO2, and there is a plasticizing effect under high pressure. Zeolite molecular sieve membranes are crystalline membrane materials of aluminosilicates formed by continuous growth of molecular sieve crystals on porous carriers in a cross-linked manner. They have a sub-nanometer pore structure with excellent chemical stability and thermodynamic stability, can achieve accurate identification and screening of molecules such as CO2 and CH4, and show a permeation rate much higher than that of polymer membranes. Early reports on zeolite molecular sieve membranes used for CO2 separation are mostly low-silicon [n(Si) / n(Al) ratio <5] zeolite molecular sieve membranes, such as NaY and chabazite, and phosphorus-aluminum molecular sieve membranes, such as SAPO-34, SAPO-17 and AlPO-18, which show high CO2 / CH4 and CO2 / N2 separation performance, far exceeding the Robeson upper limit of polymer membranes. However, the above-mentioned low-silicon zeolite molecular sieve membranes and phosphorus-aluminum molecular sieve membranes are highly hydrophilic and still face severe challenges in high-humidity flue gas carbon capture applications. Taking the SAPO-34 molecular sieve membrane with CHA topology as an example, the introduction of only 1 vol% of water vapor in the CO2 / N2 mixed gas can cause its CO2 permeation rate to decrease by 99%, while only 3 vol% of water vapor can cause the pores of the low-silicon CHA type (chabazite) molecular sieve membrane [n(Si) / n(Al) ratio = 3] to be blocked, causing it to lose its separation performance.

[0004] High-silicon zeolite molecular sieve membrane materials have a hydrophobic surface and exhibit good moisture resistance. Currently, only a small amount of all-silicon and high-silicon zeolite molecular sieve membrane materials, such as DDR and CHA, are expected to meet the application requirements of wet flue gas carbon capture. Among them, the DDR type molecular sieve membrane only has a two-dimensional pore system, and the pore permeability and gas permeability of the membrane are difficult to improve. The CHA type molecular sieve membrane with a three-dimensional pore system has a higher micropore density and pore permeability, and the prepared membrane material exhibits a higher gas permeability rate. The crystallization rate of high-silicon [n(Si) / n(Al) ratio ≥10] molecular sieves is generally low, and there are certain challenges in the synthesis of the membrane and the precise design of the microstructure. Studies have shown that in the unit cell of high silicon CHA type molecular sieve (SSZ-13), each additional Al atom will adsorb approximately 1.5 more water molecules. Kosinov et al. also found that a single unit cell of SSZ-13 molecular sieve contains 5.4 water molecules (Journal of Membrane Science, 2015, 484: 140-145). The presence of water molecules in the unit cell will greatly reduce the permeation rate of CO2. However, there is only one water molecule in a single unit cell of Si-CHA molecular sieve, which reduces the effect of the presence of water molecules on the membrane permeation rate to a certain extent. In addition, the framework and pores of the all-silicon CHA type molecular sieve do not contain any metal ions (metal ions do not change the pore size), have an electrically neutral framework structure, and the increase in CO2 permeation rate is of great significance for achieving low energy consumption and high efficiency carbon capture of flue gas.

[0005] The preparation of all-silicon CHA (Si-CHA) type molecular sieve membranes is extremely challenging, mainly because its synthesis requires the use of the traditional semi-dry colloidal fluorine mineralization route, and the viscous gel synthesis system greatly increases the probability of intercrystalline pore formation. The molecular sieve synthesis route that adds fluorides such as hydrofluoric acid as specific mineralizers is called fluorine route synthesis, and it has also become a general method for synthesizing all-silicon CHA molecular sieves and molecular sieve membranes. The literature reported so far all uses the fluorine route secondary synthesis method to prepare all-silicon CHA molecular sieve membranes. CN111530302B discloses the use of silicon hexafluoride as a fluorine source and a silicon source, and the secondary hydrothermal method to synthesize an all-silicon CHA molecular sieve membrane. The use of fluorides is not environmentally friendly. WO2017081841A1 discloses a method for preparing Si-CHA molecular sieve membranes by a conventional secondary hydrothermal fluorine route with the addition of seed crystals, and the H2 / SF6 selectivity of the prepared membrane is greater than 10. US2014315709A1 discloses a method for ultrasonically selectively depositing a layer of Si-CHA molecular sieve crystal layer and preparing Si-CHA molecular sieve membrane under the fluorine route. The document (Separation and Purification Technology, 2018, 197: 116-121) reports the preparation of all-silicon CHA molecular sieve membrane in a semi-solid gel system with hydrofluoric acid as the fluorine source. The thickness of the synthetic molecular sieve membrane is 2μm, and the CO2 / CH4 separation selectivity is as high as 130. The author also found that under high pressure and humidification, the CO2 permeation rate of the membrane is equivalent to the CO2 / CH4 selectivity and in the dry system, which fully demonstrates the moisture resistance and stability of the all-silicon CHA molecular sieve membrane. Its physical fluidity is poor, the synthesis time is long (120h) and the repeatability is difficult to guarantee.

[0006] At present, the synthesis of all-silicon CHA molecular sieve membranes still faces the following difficulties: (1) Existing reports have all prepared pure-phase all-silicon CHA crystals and membranes under the fluorine route, but the use of fluorides is extremely unfriendly to the environment. (2) All-silicon CHA crystals and membranes are prepared within a relatively low and narrow range of n(H2O) / n(SiO2) ratios (ratio = 4-7). It is difficult to form a continuous and dense membrane layer with controllable thickness in this semi-solid gel system, and the repeatability of the preparation of all-silicon CHA molecular sieve membranes is difficult to ensure. (3) The synthesis time of all-silicon CHA molecular sieve crystals and membranes is relatively long.

[0007] Since it is impossible to determine how components such as silicon-oxygen tetrahedrons are assembled into molecular sieve crystals with specific pore structures, the nucleation and crystallization mechanisms of molecular sieve crystals under different reaction conditions are still unclear (Xu Ruren et al., "Molecular Sieve and Porous Materials Chemistry", 2015, Science Press, page 281). The film formation mechanism of molecular sieve membranes is even more complicated. How to prepare all-silicon CHA molecular sieve membranes in an environmentally friendly and highly reproducible manner has always been a challenge and difficulty in research in this field. Summary of the invention

[0008] The purpose of the present invention is to provide a method for synthesizing Si-CHA molecular sieve membranes by a heterogeneous seeding method, solve the problems existing in the semi-dry colloidal fluorine mineralization route, adopt a clear liquid alkali mineralization route instead of a fluorine mineralization route, and use a heterogeneous seeding method (seeding method) instead of a secondary hydrothermal synthesis method to improve the repeatability of Si-CHA molecular sieve membrane preparation as well as membrane performance and quality, reduce the synthesis time, and make the synthesis process friendly, so as to construct a high-quality, high-performance all-silicon CHA type molecular sieve membrane.

[0009] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a method for synthesizing Si-CHA molecular sieve membrane by using a heterogeneous seed method, comprising the following steps:

[0010] (1) Preparation of MFI molecular sieve seed crystals: a silicon source, a structure directing agent SDA and water are mixed to form a sol having a molar ratio of SiO2:SDA:H2O=1:(0.02-1):(10-100), after aging under stirring at room temperature, the sol is hydrothermally synthesized at 80-200°C for 4-60h, and the product is centrifuged, washed and dried to obtain MFI molecular sieve seed crystals;

[0011] (2) Carrier pretreatment: dispersing the MFI molecular sieve seed crystals synthesized in step (1) into a solvent to prepare a seed crystal suspension, coating the seed crystals on the surface of a porous carrier, and drying to obtain an MFI molecular sieve seed crystal layer;

[0012] (3) Preparation of Si-CHA molecular sieve membrane: A silicon source, a structure directing agent SDA, an alkali source and water are mixed, and the mixture is stirred and aged for 1 to 20 hours. The molar ratio of the components of the resulting synthetic sol is: SiO2:SDA:LiOH:H2O=1:(0.1 to 1.0):(0.01 to 0.8):(15 to 500). The porous carrier coated with the seed layer in step (2) is placed in the synthetic sol and subjected to hydrothermal synthesis at a temperature of 100 to 250°C for 1 to 100 hours. After the reaction is completed, the mixture is washed to neutrality, dried and calcined to obtain the Si-CHA molecular sieve membrane.

[0013] Preferably, the silicon source is selected from silica sol, tetraethyl orthosilicate, tetramethyl orthosilicate, sodium silicate, water glass or silicon powder.

[0014] Preferably, the structure directing agent SDA is selected from one or more of N,N,N-trimethyladamantylammonium hydroxide, N,N,N-trimethyladamantylammonium bromide, N,N,N-trimethyladamantylammonium iodide, tetrapropylammonium hydroxide or tetraethylammonium hydroxide.

[0015] Preferably, in step (2), the porous carrier material is alumina, zirconia, mullite, silicon carbide or silicon oxide, or a composite thereof.

[0016] Preferably, in step (2), the porous carrier is in the form of a sheet, a tube or a hollow fiber.

[0017] Furthermore, in step (2), the porous carrier is pretreated by ultrasonic cleaning and drying before coating.

[0018] Preferably, in step (2), the mass concentration of the suspension is 0.01wt% to 0.5wt%; and the solvent is water, ethanol or isopropanol, or a mixed solvent thereof.

[0019] Preferably, in step (2), the method for coating the seed layer on the porous carrier is dip coating, vacuum suction or spin coating.

[0020] Preferably, in step (2), the size of the seeds of the MFI molecular sieve seed layer coated on the porous carrier is 50 to 1000 nm, and the thickness of the seed layer is 50 to 1000 nm.

[0021] Preferably, in step (3), the alkali source is lithium hydroxide, sodium hydroxide, potassium hydroxide or cesium hydroxide.

[0022] Preferably, in step (3), the calcination is carried out in air, oxygen or ozone atmosphere, the calcination temperature is 150-600° C., the calcination time is 5-50 h, and the heating and cooling rate is 0.2-2° C. / min.

[0023] Furthermore, the heating method used to increase and maintain the hydrothermal reaction temperature in steps (1) and (3) is oven heating, oil bath heating or microwave heating.

[0024] The method of the present invention adopts a clear liquid alkali mineralization route instead of a fluorine mineralization route, and replaces a semi-solid gel with a fluorine-free sol. The fluorine-free and fluid clear liquid can evenly infiltrate a porous carrier or a crystal layer, remove air from the surface and pores of the carrier or the crystal, and significantly improve the mass transfer rate, thereby greatly reducing the probability of intercrystalline pore formation, improving the repeatability of membrane preparation and the environmental friendliness of the process, constructing a dense all-silicon CHA-type molecular sieve membrane, and improving the performance and quality of the molecular sieve membrane.

[0025] MFI molecular sieves have a three-dimensional and uniform straight channel system in the

[100] ,

[110] and

[010] directions, while CHA molecular sieve crystals usually have a cubic block morphology, which makes it difficult for the seeds to be oriented and stacked on the carrier to form an oriented and thin seed layer like a two-dimensional material (MFI molecular sieve nanosheet). When the CHA molecular sieve membrane layer is composed of a single layer or only a few layers of crystals (submicron thick), it is difficult to stack to form a thin and oriented seed layer. In addition, the thickness of the seed layer plays a decisive role in the thickness of the membrane layer. The present invention uses a heterogeneous seed method to replace the secondary hydrothermal synthesis method to synthesize Si-CHA molecular sieve membranes, and adopts a heterogeneous seed method that constructs an ultra-thin, uniformly oriented two-dimensional MFI nanosheet seed layer to assist in crystallization to prepare a submicron thick molecular sieve film, and coordinates the two-dimensional MFI nanosheet assisted crystallization with a clear liquid alkali mineralization route to accurately reduce the thickness of the membrane layer, achieve simultaneous improvement of the permeability and selectivity of the membrane, and greatly reduce the time for synthesizing the Si-CHA molecular sieve membrane.

[0026] Beneficial effects:

[0027] (1) The present invention adopts a clear liquid alkali mineralization route instead of a fluorine mineralization route. The clear liquid with good fluidity can evenly infiltrate the porous carrier or crystal layer, remove the air from the surface and pores of the carrier or crystal, and the mass transfer rate in the liquid state is significantly higher than that in the semi-solid state, which greatly reduces the probability of intercrystalline pore formation, improves the repeatability of molecular sieve membrane preparation, and improves the quality and performance of the finished membrane. In addition, the clear liquid alkali mineralization route has a larger control space and a more effective and comprehensive means of controlling crystal nucleation, and has the advantages of high synthesis efficiency and environmental friendliness.

[0028] (2) The method of the present invention uses a heterogeneous seed method instead of a secondary hydrothermal synthesis method (seed method) to synthesize Si-CHA molecular sieve membrane, which has higher density and separation efficiency and significantly shortens the synthesis time.

[0029] (3) The Si-CHA molecular sieve membrane synthesized in the present invention can be used for carbon capture of natural gas, etc., and the separation factor of CO2 / CH4 is greater than 55. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 (a) Scanning electron microscope image and (b) X-ray diffraction image of the nano-MFI molecular sieve synthesized in Example 1.

[0031] Figure 2 These are SEM images of the (a) surface and (b) cross-section of the alumina / zirconia composite support in Example 1.

[0032] Figure 3 These are SEM images of the (a) surface and (b) cross-section of the seed layer coated on the alumina / zirconia composite carrier in Example 1.

[0033] Figure 4 This is a SEM image of the surface of the Si-CHA molecular sieve membrane prepared in Example 1.

[0034] Figure 5 This is a SEM image of the cross section of the Si-CHA molecular sieve membrane prepared in Example 1.

[0035] Figure 6 This is the X-ray diffraction pattern of the Si-CHA molecular sieve membrane prepared in Example 1.

[0036] Figure 7 ATR / FTIR graphs of the support, seed layer and membrane layer of the Si-CHA molecular sieve membrane prepared in Example 1 (synthesis time 4h, 24h). DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments are only used to illustrate the present invention, and the protection scope of the present invention is not limited to the specific embodiments, but is defined by the claims.

[0038] Example 1

[0039] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0040] (1) Preparation of MFI molecular sieve seed crystals: Silicon source tetraethyl orthosilicate, structure directing agent tetrapropylammonium hydroxide (TPAOH) and water were mixed, stirred and aged at room temperature for 6 hours to form a sol with a molar ratio of SiO2:SDA:H2O=1:0.2:18. The aged sol was charged into a reactor and hydrothermally synthesized at 140°C for 40 hours. After the reaction, the product was centrifuged, washed with water until neutral, and dried at 60°C overnight to obtain a nano-short columnar MFI molecular sieve with a size of about 200-300 nm.

[0041] (2) Carrier pretreatment: Alumina / zirconia is used as a carrier. After ultrasonic cleaning and drying of the porous tubular alumina / zirconia composite carrier, the MFI molecular sieve seed crystals synthesized in step (1) are dispersed in an ethanol solvent to prepare a 0.05 wt% seed crystal suspension solution. The seed crystals are coated on the carrier surface by dip-coating, i.e., immersion and pulling, and then dried in an oven to form a continuous and dense MFI type molecular sieve seed crystal layer;

[0042] (3) Preparation of Si-CHA molecular sieve membrane: Using silicon powder as the silicon source and N,N,N-trimethyl-1-adamantyl ammonium hydroxide as SDA, silicon powder (Fumed silica, 99wt%), lithium hydroxide (LiOH, 99.8wt%), N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH, 25wt%) and water are mixed, stirred and aged for 12h. The molar composition of the formed sol is: SiO2:SDA:LiOH:H2O=1:0.3:0.3:35. The sol is in a shaken clear liquid state. The carrier coated with the seed crystals in step (2) is placed in the sol. A stainless steel reactor containing the sol and the carrier coated with seed crystals was placed in an oven and hydrothermally synthesized at 150°C for 24 hours. After the reaction, it was cleaned, dried at 100°C, and calcined in an ozone atmosphere to remove SDA. The calcination temperature was 200°C, the calcination time was 48 hours, and the heating rate was 0.5°C / min. After calcination, an all-silicon CHA molecular sieve membrane was obtained. The prepared membrane was marked as M1.

[0043] Figure 1 The (a) scanning electron microscope image and (b) X-ray diffraction image of the nano MFI molecular sieve prepared in step (1) show that the MFI molecular sieve is short columnar with an average particle size of about 200-300 nm, and is suitable for use on a carrier with an average pore size of about 200 nm. The XRD diffraction peak of the seed crystal is completely consistent with the standard spectrum of the MFI molecular sieve, and is a pure phase MFI crystal.

[0044] Figure 2 The following are the surface and cross-sectional SEM images of the alumina / zirconia composite carrier. The average pore size of the carrier is 200 nm.

[0045] Figure 3 The surface and cross-sectional SEM images of the seed layer on the alumina / zirconia composite carrier after carrier pretreatment. The seed completely covers the carrier surface to form a continuous and dense MFI type molecular sieve seed layer with a seed layer thickness of ≤100nm.

[0046] Figure 4 , Figure 5 The surface and cross-sectional SEM images of the Si-CHA molecular film M1 synthesized by the heterogeneous seed method show that the surface of the synthesized film M1 is continuous and dense, without obvious defects, and the film thickness is about 500 nm.

[0047] Figure 6 This is the XRD pattern of the Si-CHA molecular sieve membrane M1 synthesized by the heterogeneous seed method. The diffraction pattern of the membrane layer corresponds to the characteristic peaks of the CHA structure, indicating that the synthesized membrane is a pure CHA crystal phase.

[0048] Figure 7ATR / FTIR images of Si-CHA molecular sieve membrane carrier, seed layer and membrane layer synthesized for 4h and 24h by heterogeneous seeding method (from top to bottom), 1225cm -1 It is the distinguishing peak between MFI molecular sieve and other molecular sieves. Compared with the seed layer, when the synthesis time is 4h, 1225cm -1 When the hydrothermal synthesis time of step (3) reaches 24 h, the vibration peaks of D6R (530 and 462 cm) belonging to the CHA structure can be clearly observed. -1 ), indicating that MFI seeds successfully induced the synthesis of Si-CHA molecular sieve membrane.

[0049] The gas separation performance of the membrane is represented by two parameters: gas permeation rate P and separation coefficient α. The gas permeation rate P represents the total amount of gas passing through the membrane per unit area per unit time and unit pressure, P = N / (A×△P), and the unit is mol / (m 2 s Pa); the separation coefficient α is used to evaluate the membrane separation efficiency, α = P A / P B .

[0050] The prepared all-silicon CHA molecular sieve membrane M1 was tested for gas separation performance in the CO2 / CH4 system. The test conditions were: temperature 25°C, transmembrane pressure drop of 0.2MPa, permeate pressure maintained at 0.103MPa, molar composition of 50 / 50%, and feed gas flow rate of 4L / min. The gas flow rate on the permeate side was measured with a soap bubble flowmeter, and the gas composition on the permeate side was analyzed with a gas chromatograph (Shimadzu, GC2014). The test results are shown in Table 1.

[0051] Example 2

[0052] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0053] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that the silicon source is sodium silicate, SDA is N,N,N-trimethyl-1-adamantyl ammonium bromide, the reaction temperature is 200° C., the synthesis time is 40 h, and the diameter of the obtained MFI molecular sieve seed crystals is about 1000 nm;

[0054] (2) Carrier pretreatment: The process is similar to step (2) of Example 1, except that the concentration of the seed suspension is 0.5 wt %, the solvent is isopropanol solution, and the carrier is a flaky alumina carrier;

[0055] (3) Preparation of Si-CHA molecular sieve membrane: The preparation process is similar to step (3) of Example 1, except that the silicon source is tetraethyl orthosilicate, SDA is N,N,N-trimethyl-1-adamantyl ammonium bromide, the sol molar composition is: SiO2:SDA:LiOH:H2O=1:0.1:0.1:15, the synthesis temperature is 120°C, the synthesis time is 100 h, microwave heating is used, and the prepared membrane is marked as M2.

[0056] The prepared all-silicon CHA molecular sieve membrane M2 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0057] Example 3

[0058] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0059] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that the silicon source is water glass, SDA is tetraethylammonium bromide, and the molar ratio of the formed sol is: SiO2:SDA:H2O=1:0.5:10;

[0060] (2) Carrier pretreatment: the process is the same as step (2) of Example 1;

[0061] (3) Preparation of Si-CHA molecular sieve membrane: The process is similar to step (3) of Example 1, except that the alkali source is sodium hydroxide, the silicon source is tetramethyl orthosilicate, and the sol molar composition is: SiO2: SDA: LiOH: H2O = 1:1:0.8:500. The prepared membrane is marked as M3.

[0062] The prepared all-silicon CHA molecular sieve membrane M3 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0063] Example 4

[0064] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0065] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that a sol having a molar ratio of SiO2:SDA:H2O=1:0.5:15 is formed, the reaction temperature is 80°C, the reaction time is 40 h, and the diameter of the obtained MFI molecular sieve seed crystals is about 400 nm;

[0066] (2) Carrier pretreatment: The process is similar to step (2) of Example 1, except that in step (2), the seed crystals are coated by vacuum suction method, the suction time is 60 s, the seed liquid concentration is 0.25 wt %, and the seed layer thickness is 1000 nm;

[0067] (3) Preparation of Si-CHA molecular sieve membrane: The preparation process is similar to step (3) of Example 1, except that the silicon source is silica sol, SDA is N,N,N-trimethyl-1-adamantyl ammonium iodide, the sol molar composition is: SiO2:SDA:LiOH:H2O=1:1:0.5:300, the synthesis temperature is 250°C, the synthesis time is 5h, and the prepared membrane is marked as M4.

[0068] The prepared all-silicon CHA molecular sieve membrane M4 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0069] Example 5

[0070] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0071] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that a sol with a molar ratio of SiO2:SDA:H2O=1:1:100 is formed, the reaction temperature is 200°C, the reaction time is 30 h, and the diameter of the obtained MFI molecular sieve seed crystals is about 1000 nm;

[0072] (2) Carrier pretreatment: The process is similar to step (2) of Example 1, except that the carrier is a silicon carbide carrier, the seed suspension concentration is 0.05 wt%, and the solvent is water;

[0073] (3) Preparation of Si-CHA molecular sieve membrane: The preparation process is similar to step (3) of Example 1, except that the silicon source is tetramethyl orthosilicate, SDA is a mixture of N,N,N-trimethyl-1-adamantylammonium hydroxide and tetraethylammonium hydroxide in a molar ratio of 1:1, and the molar composition of the sol is: SiO2:SDA:LiOH:H2O=1:0.5:0.8:50. The prepared membrane is marked as M5.

[0074] The prepared all-silicon CHA molecular sieve membrane M5 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0075] Example 6

[0076] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0077] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that a sol having a molar ratio of SiO2:SDA:H2O=1:0.02:50 is formed, the reaction time is 60 h, and the diameter of the obtained MFI molecular sieve seed crystals is 600 nm;

[0078] (2) Carrier pretreatment: The process is similar to step (2) of Example 1, except that the carrier used in step (2) is a hollow fiber silica / mullite composite carrier;

[0079] (3) Preparation of Si-CHA molecular sieve membrane: The process is similar to step (3) of Example 1, except that the sol aging time is 1 h, the reaction temperature is 200°C, the reaction time is 36 h, SDA is removed under oxygen atmosphere, the calcination temperature is 550°C, the calcination time is 5 h, the heating rate is 1°C / min, and the prepared membrane is marked as M6.

[0080] The prepared all-silicon CHA molecular sieve membrane M6 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0081] Example 7

[0082] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0083] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that the silicon source is silica sol, SDA is tetrapropylammonium iodide, the reaction temperature is 100° C., the reaction time is 4 h, and the diameter of the obtained MFI molecular sieve seed crystals is about 50 nm;

[0084] (2) Support pretreatment: The process is similar to step (2) of Example 1, except that the concentration of the seed suspension is 0.01 wt % and the seed layer thickness is about 50 nm;

[0085] (3) Preparation of Si-CHA molecular sieve membrane: The process is similar to step (3) of Example 1, except that the aging time is 20 h, the molar composition of the sol is: SiO2:SDA:LiOH:H2O=1:0.5:0.01:80, the reaction temperature is 100°C, the reaction time is 100 h, the calcination method is to remove SDA in an oxygen atmosphere, the calcination temperature is 450°C, the calcination time is 5 h, the heating rate is 2°C / min, and the obtained membrane is marked as M7.

[0086] The prepared all-silicon CHA molecular sieve membrane M7 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0087] Example 8

[0088] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0089] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that the reaction temperature is 100° C., the synthesis time is 50 h, and the diameter of the obtained MFI molecular sieve seed crystals is about 100 nm;

[0090] (2) Carrier pretreatment: the process is the same as step (2) of Example 1;

[0091] (3) Preparation of Si-CHA molecular sieve membrane: The process is similar to step (3) of Example 1, except that oil bath heating is used, the reaction temperature is 170°C, the reaction time is 1 h, the calcination method is to remove SDA in an ozone atmosphere, the calcination temperature is 150°C, the calcination time is 50 h, the heating rate is 1°C / min, and the prepared membrane is marked as M8.

[0092] The prepared all-silicon CHA molecular sieve membrane M8 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0093] Example 9

[0094] A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, the specific steps are as follows:

[0095] (1) Preparation of MFI molecular sieve seed crystals: The preparation process is similar to step (1) of Example 1, except that the silicon source is silicon powder and the structure directing agent is tetrapropylammonium bromide;

[0096] (2) Carrier pretreatment: The process is similar to step (2) of Example 1, except that the seed coating method in step (2) is spin coating, the seed suspension concentration is 0.03 wt%, and the solvent is water;

[0097] (3) Preparation of Si-CHA molecular sieve membrane: The preparation process is similar to step (3) of Example 1, except that the structure directing agent is removed under oxygen atmosphere, the calcination temperature is 600°C, the calcination time is 20 h, the heating rate is 0.2°C / min, and the prepared membrane is marked as M9.

[0098] The prepared all-silicon CHA molecular sieve membrane M9 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0099] Comparative Example 1 Preparation of all-silicon CHA molecular sieve membrane using fluorine-containing gel system

[0100] A method for synthesizing a Si-CHA molecular sieve membrane, the method being as follows:

[0101] (1) Preparation of CHA type molecular sieve seed crystals: Si powder (Fumed silica, 99 wt%), N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH, 25 wt%) and deionized water were mixed, stirred at room temperature until completely dissolved, and Si-CHA molecular sieve was added thereto. The mixture was heated at 60°C, stirred until dry powder, and hydrofluoric acid (HF, 40 wt%) was added thereto until the sol became neutral. The water was evaporated by heating to the required water content, and the molar composition of the synthesized sol was: SiO2:TMAdaF:H2O=1:0.8:6.5. The above sol was placed in a stainless steel reactor and hydrothermally synthesized at 150°C for 72 hours. After the reaction was completed, it was taken out, and the reaction product was centrifuged, washed to neutrality, and dried to obtain Si-CHA molecular sieve seed crystals with a seed size of about 200 to 300 nm.

[0102] (2) Carrier pretreatment: The tubular porous carrier (zirconia / alumina composite carrier, average pore size 200 nm) was ultrasonically cleaned and dried, and the Si-CHA molecular sieve synthesized in step (1) was dispersed in an ethanol solvent to prepare a seed suspension solution. A 0.05 wt% seed suspension was obtained by ultrasonic treatment. Both ends of the tubular porous carrier were sealed with polytetrafluoroethylene plugs. A layer of seed was coated on the tubular porous carrier by an immersion pulling method. After oven drying, a continuous and dense seed layer was obtained.

[0103] (3) Preparation of Si-CHA molecular sieve membrane: The preparation of sol is the same as step (1), except that the molar composition of the synthetic sol is: SiO2:TMAdaF:H2O=1:0.5:5.5; the carrier coated with seed crystals is placed in a stainless steel reactor filled with the above sol, and hydrothermally synthesized at 150°C for 36 hours. After the reaction, it is washed, dried at 100°C, and calcined in an ozone atmosphere to remove the structure directing agent. The calcination temperature is 200°C, the calcination time is 48 hours, and the heating rate is 0.2°C / min. After calcination, a Si-CHA molecular sieve membrane is obtained. The obtained membrane is marked as M10.

[0104] The prepared all-silicon CHA molecular sieve membrane M10 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0105] Comparative Example 2 Preparation of all-silica CHA molecular sieve membrane by fluorine-free flow dynamic gel system

[0106] A method for synthesizing a Si-CHA molecular sieve membrane, the method being as follows:

[0107] (1) Preparation of CHA type molecular sieve seed crystals: Si powder (Fumed silica, 99 wt%), N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH, 25 wt%) and deionized water were mixed and stirred at room temperature until completely dissolved, and Si-CHA molecular sieve was added thereto. The mixture was heated at 60°C and stirred until dry powder was obtained, and hydrofluoric acid (HF, 40 wt%) was added thereto until the sol became neutral. The water was evaporated by heating to the required water content, and the molar composition of the synthesized sol was: SiO2:TMAdaF:H2O=1:0.8:6.5. The above sol was placed in a stainless steel reactor and hydrothermally synthesized at 150°C for 72 hours. After the reaction was completed, the sol was taken out and the reaction product was centrifuged, washed to neutrality and dried to obtain Si-CHA molecular sieve seed crystals with a seed size of about 200 to 300 nm.

[0108] (2) Carrier pretreatment: The tubular porous carrier (zirconia / alumina composite carrier, average pore size 200 nm) was ultrasonically cleaned and dried, and the Si-CHA molecular sieve synthesized in step (1) was dispersed in an ethanol solvent to prepare a seed suspension solution. A 0.05 wt% seed suspension was obtained by ultrasonic treatment. Both ends of the tubular porous carrier were sealed with polytetrafluoroethylene plugs. A layer of seed was coated on the tubular porous carrier by an immersion pulling method. After oven drying, a continuous and dense seed layer was obtained.

[0109] (3) Preparation of Si-CHA molecular sieve membrane: Using silicon powder as the silicon source and N,N,N-trimethyl-1-adamantyl ammonium hydroxide as SDA, silicon powder (Fumed silica, 99wt%), lithium hydroxide (LiOH, 99.8wt%), N,N,N-trimethyl-1-adamantyl ammonium hydroxide (TMAdaOH, 25wt%) and water are mixed, stirred and aged for 6h. The molar composition of the formed sol is: SiO2:SDA:LiOH:H2O=1:0.3:0.3:35. The carrier coated with the seed crystals in step (2) is placed in the sol. The stainless steel reactor containing the sol and the carrier was placed in an oven and hydrothermally synthesized at 150°C for 36 hours. After the reaction, it was cleaned, dried at 100°C, and calcined in an ozone atmosphere to remove SDA. The calcination temperature was 200°C, the calcination time was 48 hours, and the heating rate was 0.5°C / min. After calcination, an all-silicon CHA molecular sieve membrane was obtained. The prepared membrane was marked as M11.

[0110] The prepared all-silicon CHA molecular sieve membrane M11 was tested for gas separation performance in a CO2 / CH4 system. The test conditions were the same as those in Example 1, and the test results are shown in Table 1.

[0111] As shown in Table 1, the permeation rate of the Si-CHA molecular sieve membrane synthesized in the present invention can be as high as 12.3×10 -7mol / (m 2 sPa), CO2 / CH4 separation selectivity is 124, which is higher than the separation performance of Si-CHA molecular sieve membrane prepared by the traditional semi-solid fluorine-containing route and the secondary hydrothermal method. The clear liquid with good fluidity can evenly infiltrate the porous carrier or crystal layer to remove the air on the surface and pores of the carrier or crystal, thereby improving its permeation rate; the two-dimensional MFI nanosheet assisted crystallization and the clear liquid alkali mineralization route are coordinated, and the mass transfer rate in the liquid state is significantly higher than that in the semi-solid state, which greatly reduces the probability of intercrystalline pore formation and synthesizes high-quality molecular sieve membranes (excellent separation selectivity). Si-CHA molecular sieve membranes can be effectively prepared by the heterogeneous seed method.

[0112] Table 1 CO2 / CH4 mixed gas separation performance of the embodiments and comparative examples

[0113] .

Claims

1. A method for synthesizing Si-CHA molecular sieve membrane by heterogeneous seeding method, characterized in that: The steps include: (1) Preparation of MFI molecular sieve seed crystals: a silicon source, a structure directing agent SDA and water are mixed to form a sol having a molar ratio of SiO2:SDA:H2O=1:(0.02-1):(10-100), after stirring and aging at room temperature, the sol is hydrothermally synthesized at 80-200°C for 4-60h, and the product is centrifuged, washed and dried to obtain MFI molecular sieve seed crystals; (2) Carrier pretreatment: dispersing the MFI molecular sieve seed crystals synthesized in step (1) into a solvent to prepare a seed crystal suspension, coating the seed crystals on the surface of a porous carrier, and drying to obtain an MFI molecular sieve seed crystal layer; (3) Preparation of Si-CHA molecular sieve membrane: A silicon source, a structure directing agent SDA, an alkali source and water are mixed, and the mixture is stirred and aged for 1 to 20 hours. The molar ratio of the components of the synthetic sol formed is SiO2:SDA:LiOH:H2O=1:(0.1 to 1.0):(0.01 to 0.8):(15 to 500). The porous carrier coated with the seed layer in step (2) is placed in the synthetic sol and hydrothermally synthesized at a temperature of 100 to 250°C for 1 to 100 hours. After the reaction is completed, the mixture is washed to neutrality, dried and calcined to obtain the Si-CHA molecular sieve membrane.

2. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The silicon source is selected from silica sol, tetraethyl orthosilicate, tetramethyl orthosilicate, sodium silicate, water glass or silicon powder.

3. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The structure directing agent SDA is selected from one or more of N,N,N-trimethyladamantyl ammonium hydroxide, N,N,N-trimethyladamantyl ammonium bromide, N,N,N-trimethyladamantyl ammonium iodide, tetrapropylammonium hydroxide or tetraethylammonium hydroxide.

4. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The porous carrier material in step (2) is alumina, zirconia, mullite, silicon carbide or silicon oxide, or a composite thereof.

5. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The carrier described in step (2) is in the form of a sheet, a tube or a hollow fiber.

6. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The mass concentration of the suspension in step (2) is 0.01wt% to 0.5wt%; the solvent is water, ethanol or isopropanol, or a mixed solvent thereof.

7. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: In step (2), the method for coating the seed layer on the porous carrier is dip coating, vacuum suction or spin coating.

8. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: In step (2), the size of the seed crystals of the MFI molecular sieve seed crystal layer coated on the porous carrier is 50 to 1000 nm, and the thickness of the seed crystal layer is 50 to 1000 nm.

9. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The alkali source in step (3) is lithium hydroxide, sodium hydroxide, potassium hydroxide or cesium hydroxide.

10. The method for preparing Si-CHA molecular sieve membrane by heterogeneous seeding method according to claim 1, characterized in that: The calcination in step (3) is carried out in air, oxygen or ozone atmosphere, the calcination temperature is 150-600°C, the calcination time is 5-50h, and the heating and cooling rate is 0.2-2°C / min.

Citation Information

Patent Citations

  • A Controllable Synthesis Method for All-Silica and High-Silica CHA Molecular Sieve Membranes

    CN111530302B

  • Selective sonication-assisted deposition method of inorganic particles and CHA zeolite membranes grown from seeded layers on substrates using the method and plate-like si-CHA zeolite particles used for seed layer formation and manufacturing method of the same

    US20140315709A1

  • Crystalline silica membrane complex and method for producing same, and fluid separation method

    WO2017081841A1

  • All-silicon / high-silicon molecular sieve membrane and quick preparation method thereof

    CN112744826A

  • Preparation method of all-silicon CHA molecular sieve membrane

    CN114804146A